2012
DOI: 10.3389/fphys.2012.00124
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes: Vehicles for the Transfer of Toxic Proteins Associated with Neurodegenerative Diseases?

Abstract: Exosomes are small membranous vesicles secreted by a number of cell types including neurons and can be isolated from conditioned cell media or bodily fluids such as urine and plasma. Exosome biogenesis involves the inward budding of endosomes to form multivesicular bodies (MVB). When fused with the plasma membrane, the MVB releases the vesicles into the extracellular environment as exosomes. Proposed functions of these vesicles include roles in cell–cell signaling, removal of unwanted proteins, and the transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
300
0
9

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 362 publications
(310 citation statements)
references
References 150 publications
1
300
0
9
Order By: Relevance
“…Although our transiently transfected model indicates that large aggregates of misfolded SOD1 from dead or dying cells can be efficiently taken up by neighboring cells, we and others have found that exosomal-mediated transport is relevant for misfolded protein transmission in living cells (17,20), for which we used stably transfected NSC-34 cells that show little cell death (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Although our transiently transfected model indicates that large aggregates of misfolded SOD1 from dead or dying cells can be efficiently taken up by neighboring cells, we and others have found that exosomal-mediated transport is relevant for misfolded protein transmission in living cells (17,20), for which we used stably transfected NSC-34 cells that show little cell death (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…Exosomes appear to be vehicles for transfer of toxic proteins such as amyloid-beta-derived peptides and alpha-synuclein in the brain increasing the spread of neurodegeneration in Alzheimer's disease and Parkinson's disease, respectively [95,96]. Furthermore, there is the transfer of the chemokine receptor CCR5 between cells by extracellular vesicles which is a mechanism for the spread of cellular human immunodeficiency virus 1 infection (HIV1) [97].…”
Section: (D) Pathological Relevance In the Central Nervous Systemmentioning
confidence: 99%
“…Abeta results from proteolytic cleavage of amyloid precursor 620 protein (APP). In the amyloidogenic pathway, APP in lipid rafts is cleaved first by 621 Beta--secretase and then by gamma--secretase to generate Abeta (32,33). ABeta 622 protein, and Beta and gamma--secretases are found in lipid rafts, along with 623 GM1 (33).…”
Section: Transmissible Spongiform Encephalopathymentioning
confidence: 99%
“…Amorphous non--congo red positive 627 plaques develop first, and later mature to B--sheet plaques (35). A--Beta fibrils 628 aggregate into cross--beta--pleated--sheets (36) Abeta has been found in exosomes 629 (32). 630 631…”
Section: Transmissible Spongiform Encephalopathymentioning
confidence: 99%